KAJIAN SIFAT FISIKOKIMIA EKSTRAK RUMPUT LAUT COKLAT Sargassum duplicatum MENGGUNAKAN BERBAGAI PELARUT DAN METODE EKSTRAKSI - Aisyah Tri Septiana; Ari Asnani (Agroindustrial Technology, University of Trunojoyo Madura, 2012)
Sargassum duplicatumcontain bioactive component has different polarity.The research was aimed to know the effect solvent types and extraction method toward the psychochemical characteristic of S. duplicatum extract.The result of qualitative analysis showed that all S. duplicatum extract samples contained flavonoid, tannin, saponin, and terpenoid. The best treatment were obtained from methanol treatment using one-step extraction method that gave solubility in ethanol was 39.450 percent, solubility in distilled water (aquadest) was 28.283 percent, and total phenol was 297.170 mg/g.